Regulation of body temperature and neuroprotection by endogenous interleukin-6 in cerebral ischemia - Herrmann, Oliver; Tarabin, Victoria; Suzuki, Shigeaki; Attigah, Nicolas; Coserea, Irinel Andreea; Schneider, Armin; Vogel, Johannes; Prinz, Simone; Schwab, Stefan; Monyer, Hannah; Brombacher, Frank; Schwaninger, Markus (Journal of cerebral blood flow & metabolism, 2003)
Although the function of fever is still unclear, it is now beyond doubt that body temperature influences the outcome of brain damage. An elevated body temperature is often found in stroke patients and denotes a bad prognosis. However, the pathophysiologic basis and treatment options of elevated body temperature after stroke are still unknown. Cerebral ischemia rapidly induced neuronal interleukin-6 (IL-6) expression in mice. In IL-6-deficient mice, body temperature was markedly decreased after middle cerebral artery occlusion (MCAO), but infarct size was comparable to that in control mice. If body temperature was controlled by external warming after MCAO, IL-6-deficient mice had a reduced survival, worse neurologic status, and larger infarcts than control animals. In cell culture, IL-6 exerted an antiapoptotic and neuroprotective effect. These data suggest that IL-6 is a key regulator of body temperature and an endogenous neuroprotectant in cerebral ischemia. Neuroprotective properties apparently compensate for its pyretic action after MCAO and enhance the safety of this endogenous pyrogen.
Gesehen am 22.03.2021